Pengaruh Perbandingan Ikan Tuna (Thunnus sp.) Dengan Puree Jantung Pisang (Musa Paradisiaca sp.) Terhadap Karakteristik Nugget - Ilma Daroyani, Dwi; Yusasrini, Ni Luh Ari; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPA, 2022)
This study was aimed to determine the effect ratio tuna and banana blossom puree on the characteristics of nuggets, and to determine which ratio of tuna and banana blossom puree that can produce nuggets with the best characteristics. The experimental design used was Completely Randomized Design (CRD) with 5 different treatments ratio of tuna and banana blossom puree, namely 100%: 0%; 90%: 10%; 80%: 20%; 70%: 30%; and 60%: 40%. Each treatment was repeated 3 times to obtain 15 experimental units. The data obtained were analysed using Analysis of Variance (ANOVA) and if the treatment affects the variables, the analysis will be continued using The Duncan's Multiple Range Test (DMRT). The results showed that the ratio of tuna and banana blossom puree had a very significant effect to the water content, ash content, protein content, fat content, total dietary fiber, colour and taste (hedonic test), taste and texture (score test), and gave a significant effect to hedonic of the overall acceptance. Ratio of tuna and banana blossom puree 90%:10% produce the best characteristic nuggets which were: water content of 62,89%; ash content of 2,07%; protein content of 18,26%; fat content of 2,78%; total dietary fiber of 6,74%; slightly solid texture, slightly fishy taste, and preferred colour, flavour, texture, taste, and overall acceptance.